Medication adjustment of afatinib and combination therapy with sitagliptin for alleviating afatinib-induced diarrhea in rats - Zhang, Li; Hu, Anna; Wang, Yan; Yang, Yuxin; Liu, Yalan; Xu, Lian; Wang, Lei; Cheng, Zeneng (Neoplasia (New York, N.Y.), 2023)
Afatinib, as the first-line treatment for non-small cell lung cancer (NSCLC), causes severe gastrointestinal adverse reactions that greatly affect patients' quality of life and even potentially result in treatment discontinuation. Multiple dose adjustments and concomitant use of anti-diarrheal medications are commonly employed to manage diarrhea, also allowing for a recovery period between each adjustment. However, these approaches are based on empirical guidance and still have limitations. This study aims to explore reliable approaches to alleviate diarrhea by focusing on two strategies: adjusting the dosing regimen of afatinib itself and implementing combination therapy. In this study, we firstly revealed a dose-dependent relationship between afatinib-induced diarrhea and gastrointestinal epithelial damage, resulting in atrophy, reduced expression of tight junction proteins, and increased permeability. We further found that even after discontinuation of the medication, although the severity of diarrhea had improved to baseline, the tight junction proteins and permeability of the intestinal epithelium did not fully recover, and the pharmacokinetics studies showed that drug absorption significantly increased than normal. This indicated the recovery period was longer than expected and may accelerate the occurrence of subsequent episodes of diarrhea. Hence, it would be prudent to consider adjustments to the starting dose or the recovery interval. Furthermore, we initially investigated the relationship between DPP enzyme and afatinib-induced diarrhea and found a significant decrease in plasma DPP enzyme activity following afatinib-induced diarrhea. Subsequently, we conducted continuous treatment with sitagliptin and observed significant improvement in afatinib-induced diarrhea. We observed that sitagliptin can promote the production of anti-inflammatory factors, increase the expression of intestinal epithelial tight junction proteins, and improve intestinal microbiota, further validating the mechanism through the use of GLP-23-33 as GLP-2 receptor inhibitor. In conclusion, sitagliptin exhibits promising potential as a therapeutic option for managing afatinib-induced diarrhea. Taken together, our study provides valuable insights into alleviating afatinib-induced diarrhea through both afatinib medication adjustment and sitagliptin combination therapy. [Display omitted]